Rejoinder to Igor Wysocki on Brain Death - Dominiak, Łukasz (Dialogi Polityczne, 2017)
The present text is a rejoinder to Igor Wysocki’s rejoinder published in Political Dialogues 20 to Dominiak & Szczęsny’s paper Brain Death in Japan: A Critical Approach.